Structural prediction of stabilized atomically thin tin layers - Borlido, Pedro; Huran, Ahmad W.; Marques, Miguel A. L.; Botti, Silvana (npj 2D Materials and Applications, 2019)
The family of group IV two-dimensional materials shows a rich variety of structural, electronic and topological properties. Only graphene is stable in the honeycomb structure, while buckling and dumbbell configurations stabilize silicene and germanene. Here we investigate from first principles the lowest-energy atomic arrangements of atomically-thin tin layers. Our calculations are performed with a very efficient method for global structural prediction, combined with constrains that enforce the desired one-dimensional confinement and include the effect of strain due to the substrate. We discover a series of new structures that span a large range of atomic densities and are considerably more stable than hexagonal single- or double-layer stanene, as well as dumbbell structures. The ground state, a metallic double layer with a square lattice that lies 295 meV/atom below honeycomb stanene and only 149 meV/atom above bulk α-tin, is akin to the atomic arrangement of a layer of romarchite tin oxide. Due to its enhanced stability with respect to honeycomb stanene, we propose that this structure can be easily synthesized on appropriate lattice-matched metallic substrates.
CRIS-Team Scopus Importer:2023-04-20